Respuesta :

Answer:

[tex]x \ge 1[/tex]

Step-by-step explanation:

Given

[tex]\sqrt{6(x - 1)} \div \sqrt{3x^2[/tex]

Required

x for [tex]which[/tex] the function is [tex]de fi ned[/tex]

To do this, we set the numerator root [tex]\ge 0[/tex]

So, we have:

[tex]6(x - 1) \ge 0[/tex]

Divide by 6

[tex](x - 1) \ge 0[/tex]

Solve for x

[tex]x \ge 1[/tex]

Also, we set the denominator greater than 0:

[tex]3x^2 > 0[/tex]

Divide by 3

[tex]x^2 > 0[/tex]

Take square roots

[tex]x > 0[/tex]

So, we have:

[tex]x > 0[/tex] and [tex]x \ge 1[/tex]

Combine both to give:

[tex]x \ge 1[/tex]